Preparing of saccharomyces cereviciae Synbiotic for Reducing Expermental Infection of salmonella typhimurium in Broiler 2–advanced age ( 16 -30 days): Ghada A. Qatan , Faris A. Al-Obaidi and Shahrazad M. Al-Shadeedi - Qatan, Ghada A. (The Iraqi Journal of Veterinary Medicine, 2008)
This study aimed to prepare a synbiotic of Sacch. cerevisiae and used as 0.1 and 0.2 % in feed (T2,T3) for reducing the experimental infection of Salmonella typhimurium to broiler chicks ( -6103days) by using 40 birds divided into four treatments , T1 was negative control with 0.1 % synbiotics and T4 was positive control with experimental infection only , productionand blood parameters were studied , and the results showed the following: A synbiotic of Sacch. cerevisiae was made which have 10 7 cfu ofSacch. cerevisiae and 10 mg Mannan Oligosaccharide per gram .Using 0.1 and 0.2 % of Sacch. cerevisiae synbiotic reduced experimental infection of Salmonella typhimurium via increase body weight and feed conversion anddecrease mortality and physiological stress of experimental infection.